Protection of elephants and sustainable use of ivory in Thailand. Issue 4 (14th July 2022) - Chaitae, Apinya; Gordon, Iain J.; Addison, Jane; Marsh, Helene
Abstract: The Asian elephant Elephas maximus is of cultural significance for the Thai people. The development of legal protection for elephants in Thailand dates back to the 17th century, reflecting concerns about both human livelihoods and elephant conservation. The legal status of privately owned, captive elephants differs from that of wild individuals, with consequences for the lawful use of ivory from captive animals. Prior to 2015, the lack of comprehensive measures to control the Thai ivory market enabled the laundering of illegally sourced ivory in the country. The Thai government introduced legal reforms in 2015, imposing strict controls over the possession and domestic trade of ivory from captive Asian elephants, and aligning the protection of African elephants and their ivory with CITES regulations. Nonetheless, the sustainable use of Thai ivory remains disputed, and international pressure to close the commercial trade in domestic ivory persists. Here we review this complex situation, aiming to inform future reforms. Consolidation of laws related to elephants and ivory would facilitate law enforcement and compliance. Use of an electronic database would improve the monitoring of ivory movements and aid the implementation and enforcement of laws.